The Differences of Male and Female Students’s Problem Solving Ability in Environmental Change Topic Based on Education for Sustainable Development (ESD) - Dewi Arum Budianti; Ary Susatyo Nugroho; Muhammad Syaipul Hayat (Universitas PGRI Semarang, 2023)
This study aims to determine the differences between male and female students’s problem solving abilities in environmental change topic based on ESD. This study used pre-experimental method with one group pretest – post test design. This study located at MA Darul Muqorrobin with subjects 30 students of class X who selected using a purposive sampling technique. Generally, female students’s problem solving ability is higher than male student’s, with a final value of 77.7 for male students and 82.3 for female students. Male students have an average total score higher than female students on the problem understanding indicator, namely 7.7 for male students and 7.4 for female students. In the problem-solving design indicator, female students have a higher average total score than male students, namely 6.1 for male students and 6.5 for female students. Female students have an average total score higher than male students on the indicator of carrying out problem solving, namely 5.8 for male students and 6.4 for female students. In the indicators evaluating problem solving, female students have an average total score higher than male students, namely 5.3 for male students and 5.9 for female students. The high female students’s problem solving ability due to the structure of woman’s corpus collasum which thicker than the men’s. Testosterone hormone causes men prefer learning that hands-on. The preoptic region in the men’s hypothalamus is larger than women’s so men can understand problem better than women. The interpretation of the N-Gain value is sufficient, so the learning of environmental change topic based on ESD is effective to improve problem solving ability in both students.